Cholesterol efflux capacity is impaired in subjects with an elevated Fatty Liver Index, a proxy of non-alcoholic fatty liver disease - van den Berg, Eline H.; Gruppen, Eke G.; Ebtehaj, Sanam; Bakker, Stephan J.L.; Tietge, Uwe J.F.; Dullaart, Robin P.F. (Atherosclerosis, 2018)
Non-alcoholic fatty liver disease (NAFLD) parallels the obesity epidemic and associates with components of the metabolic syndrome (MetS). Cholesterol efflux capacity (CEC) represents a key metric of high density lipoprotein (HDL) function which may predict atherosclerotic cardiovascular disease (CVD). Here we assessed the relationship of CEC with NAFLD. CEC was determined from THP-1 macrophage foam cells towards apolipoprotein B-depleted plasma among 639 subjects (454 men; 36 subjects with type 2 diabetes mellitus (T2D); 226 with MetS), participating in the Prevention of Renal and Vascular End-Stage Disease (PREVEND) study. A Fatty Liver Index (FLI) ≥ 60 was used as a proxy of NAFLD. 372 participants had a FLI ≥60, which coincided with an increased prevalence of T2D and MetS (p = 0.009 and p < 0.001), as well as with central obesity, higher systolic blood pressure, glucose, total cholesterol, triglycerides and high sensitivity C-reactive protein (hsCRP), and decreased HDL cholesterol (p < 0.001 for each). In multivariable linear regression analyses, CEC was inversely associated with an elevated FLI, when taking account of clinical covariates (fully adjusted model: β = −0.091, p = 0.043), and alternatively when taking account of systolic blood pressure, waist/hip ratio, glucose, HDL cholesterol, triglycerides and hsCRP (fully adjusted model: β = −0.103, p = 0.034). Impaired CEC is associated with NAFLD, as inferred from a FLI≥60, even when taking account of lower HDL cholesterol and enhanced low-grade chronic inflammation. Reduced CEC could contribute to accelerated CVD in NAFLD patients. •NAFLD is associated with elevations in apoB lipoproteins and low HDL-C.•Cholesterol efflux capacity (CEC) was measured in 639 subjects with suspected NAFLD.•CEC was impaired in subjects with suspected NAFLD, i.e. a Fatty Liver Index (FLI) ≥60.•CEC remained inversely associated with an elevated FLI independent of HDL-C.•NAFLD may contribute to impaired HDL function, even when taking account of HDL-C.